Численное моделирование возникновения пульсационной неустойчивости пламен в нерегулярных зернистых средах - Астахов, Даниил Сергеевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
Porous burners demonstrate oscillatory flame behavior at low flow rates. It similar to unstable combustion in narrow channels, but accompanied by complex dynamics due to the irregular porous structure, the flow field and the temperature gradient formed as a result of heat recuperation. This work is a numerical study of combustion at the pore scale, in a two-dimensional pseudo-irregular compacted layer of particles generated using the Voronoi tessellation algorithm with a constant pore diameter. The results obtained demonstrate the region of existence of unstable flame oscillations, such as a flame with repeated attenuation and ignition (FREI) depending on the variation in pore diameter and flow rate. A pulsating transient flame between stable normal flame and FREI was detected. The amplitude and intensity of such pulsations monotonically increase with a decrease in the flow rate in a narrow range. In the area of very low speeds, a mode with a stable weak flame was found.